Examining social anxiety and dual aspects of social comparison orientation: the moderating role of self-evaluation of social skills - Okano, Hirohito; Nomura, Michio (Frontiers in Psychology, 2023)
Introduction: Social comparison orientation comprises ability comparison, which entails superior and inferior ratings; and opinion comparison, which does not include such ratings. Previous research on negative emotions and the social rank theory of social anxiety indicates that social anxiety is positively associated with ability comparison. This is particularly true of individuals with a stronger sense of inferiority (e.g., lower self-evaluation of their social skills). Nevertheless, the relationship between the two aspects of social comparison orientation and social anxiety remains unclear.Methods: Two hundred thirty-eight individuals (Mage = 40.53 ± 9.78 years, 50.4% men) participated in an online cross-sectional survey questionnaire.Results: Social anxiety was positively correlated with ability comparison but not opinion comparison. The relationship between social anxiety in situations observed by others and ability comparison was stronger for individuals with lower (vs. higher) self-rated social skills.Discussion: This study showed that the two types of social comparison are differentially related to social anxiety. The findings support the social rank theory of social anxiety, which states that social comparisons involving superior and inferior ratings lead to social anxiety owing to the perception of one's inferiority. Making such social comparisons can result in heightened social anxiety, particularly for individuals with low self-evaluations of social skills. The results indicate the importance of these social comparisons in the emergence and persistence of social anxiety. Moreover, these results suggest that improving self-evaluation of social skills alleviates the positive association between comparisons involving superiority and inferiority ratings and social anxiety.